SATU DEKADE GRATIFIKASI DI INDONESIA (2010-2019) - Maya Marliana; Heti Marini (http://jurnal.untirta.ac.id/index.php/JIPAGS, 2022)
The echo of 'Bureaucracy Reform' in Indonesia, has been sounded since 2010. The implementation of a clean and serving government is the main concept in Indonesia's 'Bureaucracy Reform'. Clean here, of course, is meant to be clean from Corruption, Collusion and Nepotism, where one of the branches of this KKN action is 'Gratification'. Triggered by gratification which is associated as unethical behavior in the administration of government and/or public services, we want to get an idea of how the struggle for 'Bureaucratic Reform' compares to acts of gratification during the decade after it was proclaimed. By using James Rest's 'Four-component Analysis Model' method (1986), we hope to be able to identify the aspects that influence the emergence of ethical behavior in the administration of the state and/or public services. Based on the results of observations of the CPI Score data, Indonesia has not yet succeeded in breaking through the top 80 in terms of taking action against corruption, and until 2019 there have been prosecutions for 119 cases of bribery. In order to prevent state administration and/or public services from receiving gratification, civil servants and state administrators must cognitively consider moral awareness, moral judgment and moral motivation in the form of 'intentions' and then decide to take actions that are classified as ethical behavior or moral behavior.